Authors' reply. - Wu, S.J (IEEE Transactions on fuzzy systems)
The authors reply to comments on their article (Wu and Lin, Discrete-time optimal fuzzy controller design: global concept approach, IEEE Trans. Fuzzy Syst., vol. 10, no. 1, p. 21-38, 2002).